THE DESIGN ARGUMENT FOR GOD’S EXISTENCE: Ayatullâh Ja’far Subḥânî’s Criticism of David Hume’s Thoughts - Mukhammad Zamzami; Ghorbanali Karimzadeh Gharamaleki; Abdullah Hosseinieskandian; Fikri Mahzumi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The design argument is one of the strongest arguments to prove God's existence. It has been analyzed by various thinkers throughout the history in defense of God’s existence. However, some empiricist philosophers who do not believe in God’s existence criticized and questioned this argument. David Hume (1711-1776) is one of those who made a tremendous effort to deny God’s existence. He also criticized the design argument. Hume’s critiques have always been challenged by philosophers and God-believing theologians. This article is made to criticize Hume’s critiques on the design argument from Ayatullâh Subḥânî’s perspective using descriptive-analytical method. Hume’s objection was due to misunderstanding of the argument’s purpose and function. It should be acknowledged that this argument can easily prove God’s essence along with other arguments such as ḥudûth, necessity, and possibility. The design argument pushes us to the supernatural limits. Also, this argument is supported by experimental sciences because every new discovery made in natural sciences provides us with a new sign to prove God.